Cardiopulmonary exercise testing with an in-line filter during the COVID-19 pandemic - Bhat, R. R.; Schoenike, M. W.; Kowal, A.; White, C.; Rouvina, J.; Hardin, C. C.; Malhotra, R.; Lewis, G. D. (Circulation, 2020)
Introduction: During maximum incremental exercise expiratory flow rates increase > 10-fold and minute ventilation can exceed 100L/min, raising concern for possible spread of COVID-19 in asymptomatic patients undergoing exercise testing. Moreover, use of surgical or N95 masks that limit airflow are recognized to limit the ability to perform maximum exercise.